A comparison of the thermal comfort performances of a radiation floor cooling system when combined with a range of ventilation systems. Issue 4 (April 2020) - Liu, Jiying; Li, Zhuangzhuang; Kim, Moon Keun; Zhu, Shengwei; Zhang, Linhua; Srebric, Jelena
This study conducted a series of computational fluid dynamics simulations to evaluate the thermal comfort performance of a radiant floor cooling system when combined with different ventilation systems, including mixed ventilation (MV), stratum ventilation (SV), displacement ventilation (DV) and ductless personalized ventilation (DPV). A window temperature of 32°C and three different floor temperatures including 20, 22 and 24°C were set in summer. We used the vertical air temperature differences (VATD) at ankle and head level, the percentage of dissatisfied, the draught rate at the ankle level and the equivalent temperature as our main evaluation indices. Our results show that the VATD in DV system can reach up to about 5°C, compared with about 2°C in MV and SV systems. For the DPV system, there is only a marginal drop in the VATD. For the DV and DPV cases, with a rate of air changes per hour (ACH) of 2.4 −1, we recorded a higher draught rate at the ankle level, ranging from 6.55% to 9.99%. The lower equivalent temperature values for the foot and calf segments occur when the floor temperature is 20°C. In all cases, the equivalent temperature values of the whole body indicate an acceptable level of thermal discomfort.